Coronavirus on the global development agenda: cooperation and competition in times of pandemic - Prado Lallande, Juan Pablo (Revista Española de Desarrollo y Cooperación, 2020)
During 2020, the global development agenda was fed by an exponential dynamic of international cooperation and by different competition mechanisms of among plenty entities, both in order to confronting COVID-19. This situation inevitably distracted efforts dedicated to attend the 2030 Agenda and its SDG’s, which are other victims of the pandemic.